2022
DOI: 10.12912/27197050/152118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-Sowing Application of Mineral Fertilizers, Root and Foliar Nutrition on Productivity of Winter Tritical Plants

Abstract: The purpose of the research was to develop and scientifically substantiate the system of nutrition of winter triticale crops to optimize their production process and increase plant productivity in the Northern Steppe of Ukraine. The highest number of grains in the ear of the main and lateral stems of winter triticale was in the variants where foliar nutrition with a mixture of carbamide, magnesium sulfate and complex fertilizer Ferkrystal Summum during the 31st and 39th microphases and the variants where the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…The increase in available N in soil could be due to conjoint application of NPK, biofertilizer and organic inputs. The presence of vermicompost might have resulted in release of more nitrogenous substances in the soil and might have increased the efficiency and effectiveness of soil to hold the nutrients as reported by [21,22]. Mixing of N fertilizer with organic manures might have reduced the nitrogen losses, improved the fertilizer use efficiency thus, increasing the availability of N. Similar results were also reported by Singh et al [23,24,15].…”
Section: Available Nitrogen In Soil (Kg Ha -1 )supporting
confidence: 70%
See 1 more Smart Citation
“…The increase in available N in soil could be due to conjoint application of NPK, biofertilizer and organic inputs. The presence of vermicompost might have resulted in release of more nitrogenous substances in the soil and might have increased the efficiency and effectiveness of soil to hold the nutrients as reported by [21,22]. Mixing of N fertilizer with organic manures might have reduced the nitrogen losses, improved the fertilizer use efficiency thus, increasing the availability of N. Similar results were also reported by Singh et al [23,24,15].…”
Section: Available Nitrogen In Soil (Kg Ha -1 )supporting
confidence: 70%
“…A cursory glance at the data in Further, it was also observed that all treatment combination at 75% NPK level and 100% NPK (T1) and natural farming practice showed nonsignificant among themselves for available K in post-harvest soil. The available K content increased due to addition of organic manure and biofertilizers along with NPK which helped in the release of unavailable form of potassium to available form in the soil solution and increased the potassium content in the soil [21]. The beneficial effect of vermicompost and farm yard manure on available K may be ascribed to the direct potassium addition to the potassium pool of the soil besides the reduction in potassium fixation and its release due to interaction of organic matter with clay particles [25].…”
Section: Available Phosphorous In Soil (Kg Ha -1 )mentioning
confidence: 99%
“…Treatment methods had a different effect on crop weed infestation. This is confirmed by Bielashov et al (2022) and Kuts et al (2021). For example, in the tillering phase of barley during ploughing, the number of weeds was 9.8 pcs•m -2 when the N 30 P 30 K 30 fertilizer was applied and 11.1 pcs•m -2 when the N 60 P 30 K 30 fertilizer was applied.…”
Section: Methodssupporting
confidence: 56%
“…According to O. Bielashov et al (2022), the use of phytoremediation properties of sunflower should be balanced, since the absorption of pollutants by sunflower plants, their accumulation and entry into the food chain can cause various human diseases. Y.…”
Section: Source: Compiled By the Authors Of This Study Based On Perso...mentioning
confidence: 99%